Model Probit Binrt Bivariat pada Pemberian Imunisasi Dasar dan Air Susu Ibu - Metty Nurul Romadhona (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2015)
The fourth goal of the Millennium Development Goals (MDGs) is to reduce child mortality. One of the efforts to reduce child mortality is increasing immunity for children. Immunity for children can be obtained by providing complete basic immunization and exclusive breastfeeding This study aimed to apply the bivariate binary probit model in determining factors that affect provision of basic immunization and exclusive breastfeeding. The data source used in this research is data of the 2013 National Socio Economic Survey (SUSENAS) in South Kalimantan Province. The best model selection criterion based on the AIC (Akaike Information Criterion) values provided information that the age of first marriage, mother's education, father’s job, the birth attendants and status of the living area have significant effects on the provision of basic immunization and exclusive breastfeeding.